Hybrid TOF-PET/MRI local transceiver coil. (September 2016) - Głowacz, Bartosz; Alfs, D.; Bednarski, T.; Białas, P.; Czerwiński, E.; Gajos, A.; Gorgol, M.; Jasińska, B.; Kamińska, D.; Korcyl, G.; Kowalski, P.; Kozik, T.; et al.
Abstract : In order to enhance diagnostic capabilities Positron Emission Tomography (PET) and Magnetic Resonance Imaging (MRI) devices are combined into a single hybrid device providing an access to both metabolic and morphological information during a single examination. Typically the PET detectors are placed inside the diagnostic volume of the MRI scanner, however being outside the commonly used local transmit-receiver (transceiver) coils such as head or chest coils. Coils are made of plastic parts and metal conductors on which annihilation gamma quanta may scatter before reaching the PET detectors scintillating material. This fact could cause the worsening of PET images spatial resolution and the field-of-view for the PET detectors. We propose a solution based on a novel PET tomograph concept comprising multiple detection modules, built from polymer scintillation strip ended with silicon photodetectors, arranged circumferentially inside the working volume of the MRI local transceiver coil. The adaptive of the polymer scintillators in both shape and size properties allows for a use of a standard MRI coils constructions to be combined with PET detection system without influence on the coil shape, geometry and material properties optimized so far. Current work is focused on a dedicated detection electronics development based on silicon photodetectors arrays and digital signal processing unit that will operate in high static magnetic field as well as radiofrequency waves environment of MRI scanner. The novel approach to the hybrid local coil construction would allow for using any existing MRI system extending its functionality by the PET imaging feature. Disclosure: Authors disclose any relationship that may bias the presentation.